1975
DOI: 10.1002/app.1975.070190117
|View full text |Cite
|
Sign up to set email alerts
|

Flame‐retardant poly(ethylene terephthalate)

Abstract: SynopsisPoly(ethy1ene terephthalate) containing hexabromobenzene, tricresyl phosphate, or a combination of triphenyl phosphate and hexabromobenzene, pentabromotoluene, or octabromobiphenyl was extruded or spun at 280°C into monofilaments or lowdenier yarn, respectively. Only combinations of the phosphorus-and halogen-containing compounds resulted in flame-retardant poly(ethy1ene terephthalate) systems, without depreciating their degree of luster and color quality. The melting temperature, the reduced Viscosity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1977
1977
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…PET fibers containing hexabromobenzene, tricresyl phosphate, or a combination of triphenyl phosphate and hexabromobenzene, pentabromotoluene, or octabromobiphenyl, were studied by thermogravimetry 33. At 400 °C, which is a critical temperature for thermal decomposition of PET, the control sample showed lower weight‐loss values than those having one or both additives.…”
Section: Halogen‐containing Flame Retardantsmentioning
confidence: 99%
“…PET fibers containing hexabromobenzene, tricresyl phosphate, or a combination of triphenyl phosphate and hexabromobenzene, pentabromotoluene, or octabromobiphenyl, were studied by thermogravimetry 33. At 400 °C, which is a critical temperature for thermal decomposition of PET, the control sample showed lower weight‐loss values than those having one or both additives.…”
Section: Halogen‐containing Flame Retardantsmentioning
confidence: 99%
“…The oxygen index values were also increased; for 0, 4, and 12% phosphorus the OI numbers were 20.4, 27.5, and 32.6, respectively. Koch et al (1975) studied the reduced flammability of PET in the pres ence of a flame-retardant mixture of hexabromobenzene and triphenylphosphate. Barker (1974) has evaluated triphenylphosphine oxide as a flame retar dant for PET.…”
Section: Ementioning
confidence: 99%
“…When we applied Flory's equation for depressing the melting point in polymer-diluent systems to the PET-TBB system, our results suggested that TBB molecules, which have strong affinities for PET segments, markedly retard flammability. Thus, TBB works in the condensed phase of PET fabric.In contrast, Koch et al suggested that bromine-containing flame retardants work mainly in a gas phase and not in a condensed phase, using their thermogravimetric (TG) data from measurements at a constant heating rate [3]. They discussed the mechanism of flame retardation based on the temperatures at which flame retardants are liberated, using a comparison with the thermal decomposition temperature of PET.…”
mentioning
confidence: 94%